Peptido-metal framework based electrochemical sensor for the detection of 17- β estradiol: A potential candidate for the diagnosis of ectopic pregnancy - Giriya Ponnambalam; Stalin Selvaraj (Sensing and Bio-Sensing Research, 2025)
The development and maintenance of female sexual features depend on it. Recent investigations indicate that reduced E2 levels are correlated with markedly elevated probabilities of ectopic pregnancy. Those with E2 levels ≤100 pg/mL were more likely to experience ectopic pregnancy. So, the present work aims to develop an electrochemical sensor for detecting 17 β estradiol as a potential biomarker for identifying ectopic pregnancy. In brief, the E2 sensing were carried out using glutathione copper complex as redox mediator. The glutathione copper complex has been synthesized using simple room temperature one pot procedure and characterized using UV Visible spectroscopy, FTIR for confirming coordination. Then the morphology of glutathione copper complex was analysed using Scanning electron microscopy (SEM). From that the glutathione copper complex proposed the M:L ratio is 1:2. Then, the sensing of E2 were carried out using different electrochemical techniques, including Cyclic voltammetry and Differential Pulse Voltammetry. Our results indicated that the concentrations of E2 increases, peak current gradually decreases with the strong linear negative correlation. The inverse relationship indicates that E2 is being oxidized at the electrode surface with the help of copper complex with glutathione. Based on our findings, the LOD for E2 in PBS and artificial urine sample was found to be 0.125 pg/ml and 4.99 pg/ml respectively. Whereas LOQ for E2 in PBS and artificial urine sample was found to be 5884 pg/ml and 8969 pg/ml respectively. Our developed working electrode does not show any interference with Tyrosine(Y) and Tryptophan(W) and lead for ectopic pregnancy diagnosis.